FANATISME VIKING YOGYAKARTA TERHADAP KLUB SEPAK BOLA PERSIB BANDUNG - Lubis, Bayu Aditia Ramdani (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
The research aims to look at the fanaticism of the Yogjakarta Vikings as football supporters in Indonesia using social identity theory, which is the accumulation of various group values that are integrated with the individual (social class, family or football which is considered a very important source of pride and self-esteem). . The research approach used is qualitative. Data collection techniques consist of observation and interviews. Data analysis through data collection stages, data analysis process using reality and theory. The theoretical framework is Henri Tajfel and John Turner's social identity. The results of the research show that fanaticism is formed through regional/tribal groups as an identity that individuals have. These groups are formed because they feel they have the same beliefs, behavior, values and norms. This results in strong support among the Jogja Vikings to support their favorite team when competing. The basis for the formation of the fanaticism of the Jogja Vikings is the frequent gatherings every time Persib Bandung competes in the stadium or event, thus creating harmony. This includes social categories, such as based on nationality, race, politics, religion, values and beliefs. Social identification, of course, provides members with a sense of pride and social support. In terms of inherent culture, social identity influences individuals to become fanaticism towards a football club. Keywords: Fanaticism, Social Identity, Fans, Yogyakarya Viking and Football